Interplay Between Aging and Unloading on Oxidative Stress in Fast-Twitch Muscles - Chen, Chiao-nan (Joyce) (Oxford University Press, 2013)
This study evaluated the effect of aging on the adaptation potential of antioxidants and the accumulation of oxidative damage in fast-twitch muscles in response to non–weight-bearing conditions. Adult and old rats were randomized into 4 groups: normal weight bearing, hind-limb unloading for 3, 7, and 14 days. Activities of manganese superoxide dismutase, copper–zinc superoxide dismutase, catalase, and glutathione peroxidase and contents of glutathione, carbonylated proteins, and malondialdehyde were determined in tibialis anterior muscles. We found that the adaptability of most antioxidants in fast-twitch muscles with unloading is intact in aged rats except copper–zinc superoxide dismutase where its activity decreased with 14 days of unloading. Additionally, malondialdehyde accumulated in aged muscles with 14 days of unloading but not adult muscles. Collectively, the adaptation of copper–zinc superoxide dismutase in fast-twitch muscles with unloading is impaired with aging, which may be related to the greater accumulation of malondialdehyde.